(untitled) (The Conference Hub, 2025)
The article discusses current issues of using elements of TBL technology in teaching speaking in English classes both in comprehensive schools and in higher educational institutions of non-linguistic profile. The degree of study of the problem in the scientific and pedagogical environment is analyzed. The features of such a type of speech activity as speaking are presented.